Analyzing Waste in Emergency Radiology Services through A Lean Management Approach: A Literature Review - Cynthia Rizky Indriani; Septo Pawelas Arso; Sutopo Patria Jati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Hospitals play a strategic role in supporting promotive, preventive, curative, and rehabilitative health efforts. The Emergency Department (ED) and Radiology Unit are critical services that directly affect the speed and accuracy of diagnosis, especially in emergency cases. This study aims to evaluate the efficiency of these two units using a Lean Management approach. A systematic literature review was conducted through databases including Scopus, PubMed, and Google Scholar using the keywords “emergency department,” “radiology,” and “lean management.” Inclusion criteria consisted of English- and Indonesian-language articles published between 2015 and 2024. Article selection followed the PRISMA guidelines. A total of 250 records were initially identified, with 10 high-quality articles ultimately meeting all inclusion and quality appraisal criteria for analysis. Findings indicate that Lean Management effectively identifies process waste, particularly prolonged patient waiting times and delays in radiology reporting. Techniques such as Value Stream Mapping and Root Cause Analysis were found to streamline workflows and reduce non-productive time. The implementation of Lean Management significantly enhances the efficiency of radiology services in emergency settings by optimizing processes and minimizing waste. Continuous outcome monitoring, regular training, multidisciplinary collaboration, and information technology integration are essential to ensure sustainable and system-wide improvements.